2020
DOI: 10.1021/acs.jpcc.9b11956
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rare Earth Ions in the Prevention of Dealumination of Zeolite Y for Fluid Cracking Catalysts

Abstract: In this work, we use quantum-mechanical calculations to examine a number of possible dealumination routes in a model reminiscent of a commercial Y zeolite (Si/Al ratio of 3) as used in fluid catalytic cracking. First, we determine the distribution of Al over the zeolite lattice. The thermodynamically most stable distribution found in our calculations does not match the aluminum distribution found experimentally with NMR. We then describe the design of a periodic structure model to better fit the experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 41 publications
5
38
0
1
Order By: Relevance
“…[51] Using quantum mechanical calculations, Louwen et al reported that the improved stability of zeolite Y(Si/Al = 3) upon the introduction of La 3+ can be attributed to the increase in the energy barrier of dealumination. [14] Overall, the literature concerning the introduction of RE metal ions into faujasite suggests an increase in the stability of Al under harsh conditions.I mproved understanding of the nature of RE species and their electronic interaction with the zeolite framework over the last decade will serve to guide future advancements in catalyst stability under harsh conditions ( Figure 2). In particular,the improved stability of the zeolite framework conferred by particular metals provides new research opportunities for FCC catalysts and the next generation of naphtha conversion catalysts as refiners will increasingly need to consider the direct conversion of crude to chemicals.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…[51] Using quantum mechanical calculations, Louwen et al reported that the improved stability of zeolite Y(Si/Al = 3) upon the introduction of La 3+ can be attributed to the increase in the energy barrier of dealumination. [14] Overall, the literature concerning the introduction of RE metal ions into faujasite suggests an increase in the stability of Al under harsh conditions.I mproved understanding of the nature of RE species and their electronic interaction with the zeolite framework over the last decade will serve to guide future advancements in catalyst stability under harsh conditions ( Figure 2). In particular,the improved stability of the zeolite framework conferred by particular metals provides new research opportunities for FCC catalysts and the next generation of naphtha conversion catalysts as refiners will increasingly need to consider the direct conversion of crude to chemicals.…”
Section: +mentioning
confidence: 99%
“…Significant progress has been made in the preparation of new zeolite structures and morphologies,such as nanozeolites and hierarchical zeolites,y et their stability and regeneration require further investigation and improvement. Several strategies to address the hydrothermal stability of zeolites have been developed: [10] synthesis in fluoride media affording hydrophobic zeolites with al ow number of defects, [11] postsynthetic silane treatment to protect the zeolite surface from attack by condensed water, [12] post-synthetic modification with phosphorous, [13] or ion-exchange with rare-earth metals, [14] resulting in reduced dealumination. However, some of these methods require the use of extremely hazardous reagents,s uch as HF,a nd can result in changes to the concentration, strength and access to acid sites.…”
Section: Introductionmentioning
confidence: 99%
“…Using quantum mechanical calculations, Louwen et al. reported that the improved stability of zeolite Y (Si/Al=3) upon the introduction of La 3+ can be attributed to the increase in the energy barrier of dealumination . Overall, the literature concerning the introduction of RE metal ions into faujasite suggests an increase in the stability of Al under harsh conditions.…”
Section: High Temperature Alkane Conversionmentioning
confidence: 99%
“…Small cations La, Pr and Nd were mainly found in the site I′ in the SOD cage, whereas Ce was also located in the supercages forming CeO 2 that inhibits the migration of the cation. Louwen et al 166 found that the activation energy for zeolite Y dealumination was higher in the presence of La 3+ cations. The study was done with a realistic model of the Y zeolite, where the Al distribution matches with previously reported studies by NMR spectroscopy and differs from the thermodynamically most stable distribution, which highlights the importance of knowing the local environment of the active sites.…”
Section: Improvement Of Hydrothermal Stability By the Introduction Of Extra-framework Speciesmentioning
confidence: 99%